The Expert Validation of Virtual Reality-Based Learning Media of Flexible Manufacturing Systems (FMS) - Hatmojo, Yuwono Indro; Azis, Satria Muhammad; Fauzan, Muhammad Nur (Universitas Dharma Wacana, 2025)
The advancement of digital technology has had a significant impact on the world of education, including vocational education that requires in-depth technical understanding. In this study, Virtual Reality (VR)-based learning media is an alternative to help the process of introducing engineering components more interactively and realistically. This study aims to validate VR-based learning media called Virtual Reality Distributing Station as a learning media in learning distribution station components in the Flexible Manufacturing System (FMS). Validation is carried out through evaluation by experts with a focus on two main aspects, namely, the content aspect and the media display aspect. Material experts are experts who are experienced in teaching FMS, while media experts come from experts in the development of computer-based learning media. Data analysis is carried out based on quantitative and qualitative results obtained from expert validation. The evaluation results show that the content aspect of the material, which includes suitability and usefulness, scored 87 out of 96 (90.27%) and is categorized as